Nomenclatural revision of the names of Celtis (Cannabaceae) described for Africa, and lectotypification of one Asian name - Zamengo, Henrique Borges; Chamorro, Debora; Gaglioti, André Luiz; Pederneiras, Leandro Cardoso (Phytotaxa, 2023)
This article reviews the nomenclature of 56 names of the genus Celtis, 54 of which are native to the African continent and two natives of the Asian continent. Of these 56 names, 33 are lectotypified here. Epitypes are designated for C. africana and C. holtzii. A neotype is designated for C. toka. More than 200 types were located, most of which were previously unknown.